Decoding the Therapeutic Implications of the ERα Stability and Subcellular Distribution in Breast Cancer - Tecalco-Cruz, Angeles C.; Macías-Silva, Marina; Ramírez-Jarquín, Josué Orlando; Ramírez-Jarquín, Uri Nimrod (Frontiers in Endocrinology, 2022)
Approximately 70% of all breast cancer cases are estrogen receptor-alpha positive (ERα+) and any ERα signaling pathways deregulation is critical for the progression of malignant mammary neoplasia. ERα acts as a transcription factor that promotes the expression of estrogen target genes associated with pro-tumor activity in breast cancer cells. Furthermore, ERα is also part of extranuclear signaling pathways related to endocrine resistance. The regulation of ERα subcellular distribution and protein stability is critical to regulate its functions and, consequently, influence the response to endocrine therapies and progression of this pathology. This minireview highlights studies that have deciphered the molecular mechanisms implicated in controlling ERα stability and nucleo-cytoplasmic transport. These mechanisms offer information about novel biomarkers, therapeutic targets, and promising strategies for breast cancer treatment.